1988
DOI: 10.1111/j.1478-4408.1988.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of dyes

Abstract: Normally a combination of several dyestuffs is necessary to obtain a given colour. The behaviour of dyes in admixture is therefore of great practical interest. Level and repeatable dyeings are achieved more easily if dyes of almost equal behaviour in admixture can be selected. Most fundamental work on dyeing deals with up‐take of single dyestuffs. Papers on dye‐uptake in combination dyeings are comparatively rare. The early literature has been reviewed by Vickerstaff [1] and Peters [2]. At the end of the 60s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…One important aspect of dye compatibility in a dye combination is that the rate of dyeing of the components of a dye mixture should be similar in order to obtain an increase in the depth of dyeing by increasing the dye concentration while the hue of the resultant dyed sample remains constant . The kinetic parameters of dyeing, such as time of half‐dyeing and diffusion coefficient of individual dye component are usually used to assess the compatibility of mixture of dyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important aspect of dye compatibility in a dye combination is that the rate of dyeing of the components of a dye mixture should be similar in order to obtain an increase in the depth of dyeing by increasing the dye concentration while the hue of the resultant dyed sample remains constant . The kinetic parameters of dyeing, such as time of half‐dyeing and diffusion coefficient of individual dye component are usually used to assess the compatibility of mixture of dyes.…”
Section: Introductionmentioning
confidence: 99%
“…1 One important aspect of dye compatibility in a dye combination is that the rate of dyeing of the components of a dye mixture should be similar in order to obtain an increase in the depth of dyeing by increasing the dye concentration while the hue of the resultant dyed sample remains constant. 2 The kinetic parameters of dyeing, such as time of half-dyeing and diffusion coefficient of individual dye component are usually used to assess the compatibility of mixture of dyes. These parameters might not clearly express the compatibility characteristics of the dyes since these parameters are based on this assumption that the rate of dyeing of a dye is independent of the presence of another dye whereas the absorption behavior of a single dye is likely to be different in a dye combination.…”
Section: Introductionmentioning
confidence: 99%
“…(1) shows, it means that the ratio of the quantity of adsorbed dyes during the dyeing period would be constant. [2][3][4]…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that dyes with similar dyeing rates in individual dyeing bath exhibit different absorbing behavior in mixtures which make the prediction imprecise. [3][4][5][6][7][8] Despite some organized work on the practical concept of compatibility, especially, the published work on cationic dyes, the general quantitative aspect of this term has not been cleared. Many researchers have tried to define the compatibility of dyes by comparison of the rates of dyeing of individual dyes and have recommended simple terms such as t 50 or t 70 (time of 50% or 70% dye adsorption in comparison to dyeing equilibrium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation